Pengaruh Perendaman Benih Kaliandra (Calliandra calothyrsus) pada Konsentrasi Larutan Air Kelapa - Ben Jusuf A. Bolang; Wilhelmina Seran; Mamie E. Pellondou (Wana Lestari, 2022)
The formulation of the problem in this study is how is the effect of giving coconut woter solution concetration on the growth power of Kaliandra? This study aims to determine the effect and optimal dosage of coconut water solvent for increasing germination of Kaliandra seeds ( Calliandra calothyrsus ). The study was conducted at Pusat Persemaian Permanen Fatukoa BPDASHL Benain Noelmina for one month from February to March 2022. The method used was a fully randomized design (factorial CR) with 3 treatments and 1 control and 5 replicates. Treatments in this study included L0 (control) 0% concentration (mineral water), L1 25% concentration (coconut water 250 ml + distilled water 750 ml), L2 50% concentration (coconut water 500 ml + 500 ml water), L3 concentration 75% (Coconut water 750 ml + Aquades 250 ml). The data obtained were further tested using Analysis of variance with Duncan’s Multiple Range Test (level 5%). The results showed that the concentration of the coconut water solvent had a very significant impact on the germination power and germination value of seeds, but no significant impact on the germination rate index of seeds with 50% concentration L2 treatment (coconut water 500ml + 500ml Aquades) as optimal dose concentration with increasing germination of Kaliandra ( Calliandra calothyrsus ) seeds.